(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Present study is an effort toknow the relationship of self efficiacy with the emotional suffering of theindividuals .It can be further used to control the impact of depression andparenting style on the individuals. In this study the researcher examined thelevel of self-efficacy and its relation with individuals behavior, attitude,health etc.. The researcher examined the self efficiacy and Adolescents behaviour exposed to different parentingstyle. It is also cocluded that self efficiacy effect the individual emotionswith respect to age, gender and profession as well. Authoritative parentscompared to authoritarian or permissive parents may be protected from a numberof problematic behavioral outcomes. Authoritative parenting has been positivelylinked to psychosocial competence, academic success, and fewer internalizingproblems .The findingsfurther revealed that mild, moderate and severe depression are negativelyrelated with self-efficacy of an individual. This study can be further usefulto researchers, psychologists, councellors etc.